Pemanfaatan Media Sosial Tiktok untuk Membangun Kepercayaan Diri Remaja di SMK Negeri 2 Blora - Siti Umi Nuraini; Iky Putri Aristhya (INDO PUBLISHING, 2025)
This study aims to explore how the social media platform TikTok can build self-confidence among adolescents, particularly students at SMK Negeri 2 Blora. TikTok users often express themselves through various types of content, such as singing, dancing, hijab tutorials, cooking, and more. This research employs a qualitative approach with a narrative method. Data were collected through interviews, observations, and documentation. The data analysis involved stages of data collection, reduction, presentation, and conclusion drawing. To ensure data validity, source triangulation was used by involving informants with diverse backgrounds and experiences in using TikTok. The results show that TikTok helps expand editing skills, serves as a means of social interaction, and enhances self-confidence through positive feedback from other users. Creativity and communication skills also improve, leading students to be more active in content creation. Attitudes toward appearance are also influenced; some students adopt a relaxed approach focusing on comfort, while others are motivated to follow viral trends. Negative comments from netizens can lower self-confidence and affect students' emotional conditions. TikTok is also used for trading, entertainment, and creating educational content that supports school learning. The self-confidence developed through these experiences encourages students to explore and develop their talents, with the potential to become content creators in the future.